2012
DOI: 10.1111/j.1439-0507.2012.02188.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and expression of ALS and HWP1 genotypes in Candida albicans strains isolated from Mexican patients suffering from vaginal candidosis

Abstract: Summary To detect the frequency and expression of eight ALS (agglutinin‐like sequence) genes and the HWP1 genotype in a group of Candida albicans strains isolated from Mexican women suffering from vaginal candidosis. A group of 264 women (age 15–57 years) with vaginal infections were evaluated. C. albicans was identified by PCR amplification of the rRNA internal transcribed spacer regions ITS1 and ITS2. The ALS and HWP1 genes were identified by conventional PCR, and their expression levels were determined by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
0
16
1
1
Order By: Relevance
“…C. albicans strains were identified by the API 20 C Aux test (bioMerieux, Durham, NC, USA), germ tube test [11], and PCR amplification of ITS1 and ITS2 rRNA loci (the primers are shown in Table 1) [14]. The DNA of the strains was extracted by boiling, as described by Paniagua-Contreras et al [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…C. albicans strains were identified by the API 20 C Aux test (bioMerieux, Durham, NC, USA), germ tube test [11], and PCR amplification of ITS1 and ITS2 rRNA loci (the primers are shown in Table 1) [14]. The DNA of the strains was extracted by boiling, as described by Paniagua-Contreras et al [15].…”
Section: Methodsmentioning
confidence: 99%
“…The expression of ALS and SAP gene families in C. albicans of vaginal origin has recently been studied [11, 12]. Likewise, the gene expression patterns of the LIP and PL family, which are associated with the formation of biofilm during infection, have been studied [13].…”
Section: Introductionmentioning
confidence: 99%
“…In C. albicans , the Als family is involved in the adhesion mechanism and can be regulated by environmental conditions (Verstrepen & Fink, ). ALS1 was the most frequently detected gene within the ALS family (Monroy‐Pérez et al, ), and an increased expression of ALS1 in biofilms compared with the planktonic cells was demonstrated (O'Connor et al, ). Alsteens, Van Dijck, Lipke, and Dufrêne () found that Als1 leads to the almost full recovery of the cohesive adhesion at short distances in C. albicans .…”
Section: Discussionmentioning
confidence: 99%
“…33) ALS gene family, the member encoding cell-wall glycoproteins, is an important factor for the adhesion of C. albicans. 34,35) It has been reported that ALS1 gene is expressed in the earlier stage of biofilm formation, 36) and ALS3 gene is mainly up-regulated in the mature biofilm. 37) HWP1 gene could also regulate the adhesion of C. albicans to epithelial cells by Hwp1 protein.…”
Section: Discussionmentioning
confidence: 99%